WILL THE SPIRIT OF VATICAN II SURVIVE IN THE CHURCH? - Weisner, Christian (Asian Horizons, 2018)
The 5th anniversary of the election of Pope Francis on March 13, 2018 showed quite a mixed assortment of both achievements and shortfalls of this pontificate that are very different to the previous ones. Despite very serious and long lasting problems in the Vatican and in many local churches Pope Francis has brought a change of mood into the Church that no one ever before had thought to be possible. From the perspective of the international reform movement “We Are Church,” the author undertakes to take stock of the complex and highly dynamic processes within the church, which in times of world political unrest also have effects far beyond the inner-church space. What is needed on the different levels of the Church to take up the processes that are necessary for the Roman Catholic Church to find a new and more positive role in the rapidly changing global human community?